Birds as indicators of high biodiversity zones around the Middle Pleistocene Qesem Cave, Israel. (9th November 2016) - Sánchez-Marco, Antonio; Blasco, Ruth; Rosell, Jordi; Gopher, Avi; Barkai, Ran
Abstract: Israel is part of a corridor connecting Africa and Euro-Asia that has also been a major migratory route of birds throughout the Quaternary. Very few Middle Pleistocene sites have a large enough record of avian species to provide a taxonomic composition of ornithic paleocommunities to explain their geographic distribution and the human uses of birds in the Middle Pleistocene. The inspection of the fossil remains of birds from Qesem Cave has allowed the identification of fourteen taxa including residents and migratory birds that are typical dwellers of open country, cliffs and stony ground, woodland and bushland, bodies of water and corresponding vegetated fringes. Some of the migratory taxa identified are rare or accidental at present, and this may indicate different climatic conditions in the regions where these birds lived during the other seasons. The sample of avian taxa recorded at Qesem Cave is representative of several habitats and phenological statuses As all other finds at the cave were transported by humans as indicated by some taphonomic features, the sample of bird bones presented here is influenced by the humans as bioaccumulators, as expected in archaeological sites.